Experimental analysis of fan noise and performance at the EESC-USP Fan Rig Workbench - Rocamora Junior, Bernardo Martínez (2019)
The study of turbofan aeroacoustics has become important in academia and industry as noise from other aircraft sources, as jet noise, have been reduced. The EESC-USP Fan Rig is a long-duct low-speed fan experimental setup recently built at the Department of Aeronautical Engineering of the University of São Paulo. The objective is to provide a facility for studying fan aeroacoustics with a flexible configuration that allows changes in operational conditions and geometry of the rig so that each of the noise sources can be treated separately. In this work, three experimental campaign were taken aiming to extend the knowledge of this workbench capabilities and to observe the effect that some parameters can have on noise generation. A performance campaign was carried out to characterise the effects of controllable parameters on the aerodynamic characteristics of the flow. Starting from unrestricted flow to 70% area constraint, and a range of fan speeds, several flow measurements that could be translated into performance quantities were taken: volume flow rate, fan total and static pressures, compression ratio, total and net power, and efficiency. The measured compression ratio ranged from 1.00 to 1.02, with maximum axial Mach of 0.13 and maximum total efficiency of 65%. The surge effect, an unstable configuration characterised by rotor blades stall was also observed. Significant differences in fan performance due to the installation of an Inlet Control Device (ICD) and the rotor-stator spacing were not found, except under surge conditions. A parametric campaign was carried out exploring the effects of fan rotational speed, fan loading and rotor-stator spacing. Acoustic measurements were taken using an array of 77 wall-mounted microphones to provide a baseline data set for future comparisons. Hereby, data was processed to obtain the modal decomposition and power spectrum for each configuration. The last proved useful to compare tonal and broadband noise for each configuration. Experimental results indicate that changes in fan rotational speed scale noise generation mechanisms proportionally, do not affect noise spectral shape, and in consequence, are not useful to distinguish noise mechanisms. Although throttling does not seem to exhibit a clear effect on fan noise, it turns out that it is a good approach for cross-comparisons of other parameters\' effect on fan noise, because of its direct modification on the flow structure within the duct. Results also showed that increasing rotor-stator spacing reduces both blade passing frequencies tone levels and the acoustic power of the interaction modes, which are in agreement with results obtained by similar test facilities. In this work a instrumented stator vane was designed using recently available technologies, as 3D printing and the use of MEMS microphones, to measure this pressure fluctuations. Phase-averaging and the signal from a hall sensor were used to separate broadband content in time series. Broadband level distribution were analysed for two span lines of the instrumented stator vane and for a reference microphone located in the inlet antenna. Broadband levels increased with the increase in fan speed and its distribution over these span lines maintained its shape for different speeds. Cross-correlation of the microphones were calculated and showed decay of zero-delay cross-correlation with increase in distance between microphones over the vane. And, finally, the integral length scale, obtained by the integration of zero-delay cross-correlation curve, showed decay with increase in fan speed. The data generated by this work showed good agreements with what was expected from the literature and will help as input data to the semi-analytical and semi-empirical models that are being developed in parallel by the research group.